Glycerol acetylation over yttrium oxide (Y2O3) catalyst supported on palm kernel shell-derived carbon and parameters optimization studies using response surface methodology (RSM) - Fidelis Uchenna, Amadi; Irmawati, Ramli; Taufiq-Yap, Yun Hin; Mohd Izham, Saiman; Nda-Umar, Usman Idris (Elsevier, 2023)
A biomass derived carbon supported yttrium oxide catalyst (Y2O3/PKS-T700) was synthesized and evaluated in glycerol acetylation reaction using four-factor, two-level face-centred central composite design (24 CCD) of the response surface methodology (RSM). The catalyst exhibited high glycerol conversion (GC) (99.8%) and product selectivity of 11.1%, 60.2%, and 29.6% monoacetin (MA), diacetin (DA) and triacetin (TA) under optimized conditions of temperature 130 ℃, glycerol-to-acetic acid molar ratio 1:12 and catalyst loading 0.5 g in 5 h reaction time. The catalyst was synthesized via carbonization of palm kernel shell (PKS), impregnated with 15 wt% yttrium oxide (Y2O3) and calcined appropriately. The synthesized catalyst was further characterized by N2 physisorption analysis (BET surface area), X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDX), Fourier transform infra-red (FTIR), and temperature programmed desorption-ammonia (TPD-NH3). Results revealed that the catalyst is more of mesoporous material with large surface area, good pore volume and average size distributions. It is thermally stable with good acidity and various functional groups. On subjecting the catalyst to a reusability test in three (3) reaction cycles under the optimal conditions, it was found to maintain good acetylation reaction with little degradation.